2022
DOI: 10.3390/pathogens11040458
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Different Betanodavirus RGNNV/SJNNV Reassortant Strains in European Sea Bass

Abstract: European sea bass (Dicentrarchus labrax) is an important farmed marine species for Mediterranean aquaculture. Outbreaks of betanodavirus represent one of the main infectious threats for this species. The red-spotted grouper nervous necrosis virus genotype (RGNNV) is the most widely spread in Southern Europe, while the striped jack nervous necrosis virus genotype (SJNNV) has been rarely detected. The existence of natural reassortants between these genotypes has been demonstrated, the RGNNV/SJNNV strain being th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
(69 reference statements)
1
10
0
Order By: Relevance
“…In vivo challenges have shown that European sea bass juveniles are much more susceptible to RGNNV than to SJNNV, correlating with European sea bass well‐known susceptibility and in vitro studies. Interestingly, different RGNNV/SJNNV strains produced intermediate mortalities, 34,60–62 again as in the in vitro study, 59 whilst SJNNV/RGNNV strain produce roughly the same mortality as the SJNNV one. This variability emphasizes the relevance of possible point mutations in the virulence of reassortant strains.…”
Section: Pathogenicity and Host‐specificity Of Nnv Reassortantssupporting
confidence: 59%
“…In vivo challenges have shown that European sea bass juveniles are much more susceptible to RGNNV than to SJNNV, correlating with European sea bass well‐known susceptibility and in vitro studies. Interestingly, different RGNNV/SJNNV strains produced intermediate mortalities, 34,60–62 again as in the in vitro study, 59 whilst SJNNV/RGNNV strain produce roughly the same mortality as the SJNNV one. This variability emphasizes the relevance of possible point mutations in the virulence of reassortant strains.…”
Section: Pathogenicity and Host‐specificity Of Nnv Reassortantssupporting
confidence: 59%
“…Overall, these viral features influence important biological characteristics, such as host range, pathogenicity, and antigenic properties [ 10 , 33 , 34 ]. Recently, NNV coat-protein structure prediction showed that amino acid substitutions could play a role in affecting the hydrophobicity varying in the SJNNV, RGNNV, and reassortant strains [ 35 ]. This study focuses on the relationship between amino acid sequence charge and strain virulence; however, a change in the amino acid chemical characteristics could also affect the disinfectant’s effectiveness against the two tested viral strains.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the recent application of whole genome sequencing (WGS) to the study of aquatic viruses is gaining importance due to the large amount of information that it could generate. Accordingly, the WGS has permitted the identification of variable amino-acid residues probably correlated to the NNV virulence and pathogenicity thanks to the analysis of the NNV reassortant strains’ RdRp and capsid protein physico-chemical characteristics [ 162 ]. In particular, the amino acids (aa) 247 and 270 of capsid protein have been identified as putative viral receptor binding sites; accordingly, substitutions at these positions could affect the virus–host interaction.…”
Section: Nodaviridaementioning
confidence: 99%
“…In particular, the amino acids (aa) 247 and 270 of capsid protein have been identified as putative viral receptor binding sites; accordingly, substitutions at these positions could affect the virus–host interaction. In addition, Biasini and colleagues [ 162 ] speculated on the potential existence of additional interesting residues that are all exposed on the outside of the structure of the trimeric P-domains. In particular, seven variable amino acids were identified and it was possible to speculate using protein-structure prediction that changes in these positions alter the hydrophobicity and the steric hindrance of the exposed surface region, changing the physiochemical properties of the capsid protein.…”
Section: Nodaviridaementioning
confidence: 99%